2023
DOI: 10.1523/eneuro.0097-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Increased Physiological GDNF Levels Have No Effect on Dopamine Neuron Protection and Restoration in a Proteasome Inhibition Mouse Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disease that comprises a range of motor and non-motor symptoms. Glial cell line-derived neurotrophic factor (GDNF) promotes the survival of dopamine neuronsin vitroandin vivo, and intracranial delivery of GDNF has been tested in six clinical trials for treating PD. However, clinical trials with ectopic GDNF have yielded variable results, which could in part result from abnormal expression site and levels caused by ectopic overexpression. Therefore, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Here we injected AAV-Cre, this time into the NAc of GDNF cKO animals [49], to specifically target accumbal GDNF (Figure 3A). As shown on Figure 3B, Gdnf mRNA expression, which is known to correspond to GDNF protein level in mouse brain and other tissues [38,39,49,52] was successfully reduced by about 70-80% in the NAc via AAV-Cre injections. We next followed extinction over the next month before administering half the original dose of cocaine to reinstate preference (Figure 3A).…”
Section: Gdnf Cko Mice Upon Aav-cre Delivery Have About 70-80% Reduct...mentioning
confidence: 89%
“…Here we injected AAV-Cre, this time into the NAc of GDNF cKO animals [49], to specifically target accumbal GDNF (Figure 3A). As shown on Figure 3B, Gdnf mRNA expression, which is known to correspond to GDNF protein level in mouse brain and other tissues [38,39,49,52] was successfully reduced by about 70-80% in the NAc via AAV-Cre injections. We next followed extinction over the next month before administering half the original dose of cocaine to reinstate preference (Figure 3A).…”
Section: Gdnf Cko Mice Upon Aav-cre Delivery Have About 70-80% Reduct...mentioning
confidence: 89%
“…Hence, here we performed an exploratory study to see if and how methamphetamine, applied at the doses and application regimen used in the above studies to induce SCZ-like behavior in animals, induces and modulates the expression of genes related to the GDNF system. As multiple studies reveal that Gdnf mRNA levels correlate with GDNF protein levels in the mouse brain [ 2 , 14 , 73 , 74 ], in this current exploratory study, we decided to measure Gdnf mRNA levels. Additionally, previous studies have demonstrated that Gfra1 and Ret mRNA levels also correlate with protein levels in mice [ 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%